Stem cell ethics - McLaren, Anne (Henry Stewart Talks, 2007)
Stem cell biology, Therapeutic possibilities, Ethical concerns, Personal ethics, Research ethics, Moral status of human embryo, "Spare" embryos, Research embryos, Nuclear transfer embryos, Legal situation in different countries, Social ethics